POTENSI TEPUNG TEMPE SEBAGAI ESTROGEN ALAMI TERHADAP UTERUS MENCIT PREMENOPAUSE - Primiani, Cicilia Novi (Sains & Matematika, 2013)
Syntetic estrogen hormone is commonly used by women by and in their menopause cycle to overcome the problems related to menopause. Women make use of this syntetic estrogen hormone for a reason that it is easy to get, cheap and its easy application. This syntetic estrogen hormone can eventually result in side-effects. Powder of tempe has become the natural stuff with isoflavon, a chemical blend which is sturcturally fit to estrogen hormone. The objective of this research was to measure the effect of tempe starch towards the endometrium uterus of mice. The research applied experimental approach with completely randomized design with one factor of the dossage of tempe starch by 0.2 g/kg, 0.4 g/kg, and 0.6g/kg. The samples were 24 female mice of 12 months, which were divided into 4 groups of treatment with 6 times of application. The tempe powder was applied for 24 days. Surgery was was done on the 25th day. Histology of uterus was made under colouring technique of Hematoxilin Eosin (HE). The results showed that there were miometrium uterus and uterine gland proliferation. Based on the result, can be concluded that tempe powder can be used as natural estrogen.